2019
DOI: 10.1111/asap.12172
|View full text |Cite
|
Sign up to set email alerts
|

Marriage Equality: On the Books and on the Ground? An Experimental Audit Study of Beliefs and Behavior towards Same‐Sex and Interracial Couples in the Wedding Industry 

Abstract: In the United States, same‐sex and interracial couples benefit from federal court decisions recognizing and protecting their marital unions. Despite these legal protections, prejudiced beliefs and subtly‐biased behavior toward these groups may still be socially normative. The present studies surveyed Americans’ beliefs about the acceptability of prejudice toward same‐sex, interracial, and white heterosexual couples and then examined actual behavior among wedding venue professionals towards them. In Study 1, Am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…In 2018 LGBT individuals made up approximately 20% of all hate crime incidents according to FBI statistics (Federal Bureau of Investigation, 2018) even though they make up only about 4.5% of the population (Newport, 2018). And, although same-sex marriage has been legal in the United States since 2015, a recent audit study revealed that same-sex couples continue to experience more discrimination from wedding industry professionals than heterosexual couples (Kroeper et al, 2019). Furthermore, only recently did the Supreme Court establish that the Civil Rights Act of 1964 applies to sexual orientation and gender identity ( Bostock v. Clayton County , GA, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In 2018 LGBT individuals made up approximately 20% of all hate crime incidents according to FBI statistics (Federal Bureau of Investigation, 2018) even though they make up only about 4.5% of the population (Newport, 2018). And, although same-sex marriage has been legal in the United States since 2015, a recent audit study revealed that same-sex couples continue to experience more discrimination from wedding industry professionals than heterosexual couples (Kroeper et al, 2019). Furthermore, only recently did the Supreme Court establish that the Civil Rights Act of 1964 applies to sexual orientation and gender identity ( Bostock v. Clayton County , GA, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As a correspondence version of an audit study (Gaddis, 2018), in this study, we sent a fictitious inquiry to churches via e-mail from an invented person who was church shopping and soliciting information about the church's perspectives on homosexuality. Audit studies are especially good at establishing the presence of heterosexism in institutions, but this approach has mostly been used in previous research to study discrimination in the labor market (Tilcsik, 2011), the enrolling of children of gay parents in schools (Diaz-Serrano & Meix-Llop, 2016), the wedding industry (Kroeper, Muenks, & Murphy, 2019), and finding gay-affirming psychologists (Shin et al, 2020). Audit studies have never explored religious climates for sexual minorities.…”
Section: Methodsmentioning
confidence: 99%
“…In professional contexts, they experience hiring discrimination, heterosexist harassment, exclusion in valued domains (e.g., science, technology, engineering, and mathematics [STEM]), and a lack of support in education (Kosciw et al, 2012;Mishel, 2016;Patridge et al, 2014;Rabelo & Cortina, 2014). Furthermore, despite the legalization of same-sex marriage, same-sex couples continue to encounter bias in the wedding industry (Kroeper et al, 2019).…”
Section: Sexual Stigma Todaymentioning
confidence: 99%